A multi-scalar reassessment of dietary isotopic variability in bioarchaeology: Differentiating secular and inter-individual variation. (May 2022) - Greenwald, Alexandra M.; Burns, Gregory R.; Eerkens, Jelmer W.; Bartelink, Eric J.
Abstract: Stable isotope analysis has become routine in bioarchaeology and is used to reconstruct diet because it allows comparisons at inter- and intra-individual, as well as at population scales. Isotopic variation between individuals within a population is sometimes attributed to social status, or economic or subsistence specialization. However, we demonstrate that aggregating individuals within even culturally relevant time periods may confuse secular resource availability with behavioral specialization. We use both real data from prehistoric California and simulated data generated from a newly created Bayesian multi-level model to demonstrate how conflation of temporal and population scales can artificially inflate dietary variability for some populations. Our conclusions suggest that stable isotope analyses benefit from intra-individual sampling and AMS radiocarbon pairing, which aids in achieving the temporal resolution needed to infer population-scale specialization or status-based differences. Highlights: Burial populations are palimpsests of life history and secular dietary variability. Simulation shows conflation of scales introduces artificial dietary variability. Third molar-bone pairings show intertemporal dietary variability of adult foragers. Stable isotope analyses benefit from intra-individual samples and AMS pairing.